From Dictatorship to Democracy in Portugal: The use of Communication as a Political Strategy - Silva, CÃ©lia Maria Taborda da (Richtmann Publishing, 2012)
Like in every Fascist Regime, with its wide range of limited freedom, in Portugal, the New State forbade the freedom ofspeech and started controlling the Media, by using them to promote the Regime. The political speeches by AntÃ³nio de Oliveira Salazarwith the old political ideas of â€œGodâ€, Homelandâ€ and â€œFamilyâ€ of the authoritarian Regimes became state dogmas from the thirties of the20th century on. As Salazar stated, â€œ Only what we know that exists truly existsâ€. According to this thought a great propaganda strategy ofabsolute certainties was created. The State even created a Secretariat for the National Propaganda which aimed to frame the socialeveryday life into the spirit of the Regime. From the forties on, due to international happenings there is a decrease of the ideologicalpropaganda speech of the Government, since the main aim was the political survival. The fall of Dictatorship, in April 1974, made thefreedom of speech possible. However there wasnâ€™t a State impartiality regarding the Media. The revolution strategists immediately usedthe radio and the newspapers to spread news pro the political rebellion and the television to present themselves to the country. It isobvious that with the abolition of censorship there was a radical change in the system of political communication. But a long time ofDemocracy was necessary for the Media not to suffer political and governmental pressure.